A retrospective study of animal leptospirosis in Kazakhstan - Kirkimbayeva, Zhumagul; Biyashev, Birzhan; Yermagambetova, Svetlana; Kuzembekova, Gulnur; Abdeliev, Bek (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The purpose of the paper was to monitor the disease incidence in farm and wild animals in some areas of Kazakhstan, which are most susceptible to leptospirosis, and the typification of isolated pathogens, carried out under the scientific and technical program “Studying the epizootological characteristics of the country territory on particularly dangerous diseases and developing veterinary and sanitary measures to improve their effectiveness” in 2021–2023. Materials and Methods: The material included the reports of veterinary laboratories on leptospirosis in recent years, as well as laboratory tests on samples carried out at the “SANA” research and development enterprise. During this period, 6,701 serum samples from farm animals and 86,651 serum samples from rodents were tested by enzyme-linked immunosorbent assay. Results: The serological results showed antibody titers in the blood of 6.32% of cattle, 5.4% of sheep, 4.2% of horses, and 1.8% of pigs. The highest number of positive samples were found in Turkestan (12.3%), Almaty (11.7%), and Kyzylorda (11.4%) regions. Infection in rodents was lower and ranged from 0.34% to 0.07% during these years. The population of leptospira-causing diseases of animals on the territory of the country is represented by 8 serogroups. Studies in 2022 on the detection of pathogenic leptospires by polymerase chain reaction in 350 samples of blood serum from animals and 350 samples of biomaterial from rodents from different regions of Kazakhstan were negative. Conclusion: Studies conducted as part of this work will help reduce the incidence of disease among the population and animals in Kazakhstan. Adv. Vet. Anim. Res., 11(2): 439-448, June 2024 http://doi.org/10.5455/javar.2024.k793